On Some Grüss-Type Fractional Inequalities Using Saigo Fractional Integral Operator - Vaijanath L. Chinchane; Deepak B. Pachpatte (Journal of Mathematics)
The main aim of this paper is to establish some new fractional integral inequalities of Grüss-type via the Saigo fractional integral operator.